Carrot cake murder ebook - Fluke, Joanne (Hannah Swensen Mystery, 2009)
Between baking up a storm for The Cookie Jar and unraveling the mystery of her cat Moishe’s recent strange behavior, Hannah Swensen has a lot on her plate. But she’ll always make time for her business partner, Lisa, who’s in the midst of preparing for a big family reunion. Everyone is delighted when Lisa’s long-lost uncle makes a surprise appearance. No one has heard from Gus in twenty-five years. Uncle Gus is immediately the hit of the reunion. He’s almost as popular as Hannah’s scrumptious carrot cake, which is also Gus’s favorite dessert. But the next morning, as the whole family gathers for the group photo, one person is missing. Hannah offers to track down Uncle Gus, but her search leads to a shocking find. Over by the bar at the pavilion, she spots two slices of her infamous carrot cake, frosting-side down on the floor—and Gus’s corpse with an ice pick jutting out of his chest! Now Hannah’s got to sift through a long list of suspects to find a killer—even if it could mean a recipe for her own demise…